Thermal studies, degradation kinetic, equilibrium solubility, DFT, MIR, and XRPD analyses of a new cocrystal of gemfibrozil and isonicotinamide - Holanda, Bruno B. C. [UNESP]; Alarcon, Rafael T. [UNESP]; Gaglieri, Caroline [UNESP]; de Souza, Aguinaldo R. [UNESP]; Castro, Ricardo A. E.; Rosa, Paulo C. P.; Tangerino, Débora J. A.; Bannach, Gilbert [UNESP] (Springer Nature, 2019)
A synthesis of a novel pharmaceutical cocrystal of the gemfibrozil (GEM) with the isonicotinamide (INCT) as coformer was carried out using the mechanochemical method of solvent drop grinding. The cocrystal formation was evidenced using the X-Ray powder diffraction, medium infrared spectroscopy, computational methods (DFT), simultaneous thermogravimetric-differential thermal analysis (TG/DTG–DTA), and differential scanning calorimetry. The association of techniques used to analyze all proportion synthetized (GEM:INCT—5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, 1:5) showed formation of the cocrystal in the proportion of 1 mol:1 mol. Furthermore, kinetic studies were performed to determine the stability of the cocrystal formed, possible shelf time (5% degradation), and best storage temperature. The dissolution profiles of GEM and GEM:INCT were collected using 0.1 M HCl, pH 4.5 sodium acetate buffer, water, and potassium phosphate buffer at pH 5.8, pH 6.8, and pH 7.4. The results demonstrate that the cocrystal exhibits superior apparent maximum solubility relative to the pure drug with a high solubility in alkaline environment. Finally, the study shows that the cocrystal of gemfibrozil with isonicotinamide can be applied in new solid oral dosage formulations of enhanced bioavailability.
Keywords: Cocrystal; Gemfibrozil; Isonicotinamide; Non-covalent interactions; Solubility studies